Utilization of IoT Technology based on Sensors and Arduino for Observation of Industrial Liquid Waste Pollutants in Environmental Water - Vemy Nathasya; Suroso Suroso; Irawan Hadi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Water plays a vital role in human life. Based on the Regulation of the Minister of Health of the Republic of Indonesia No. 416 / MENKES / PER / IX / 1990, the criteria for clean and healthy water are clean and clear, tasteless, free from odors, toxic substances, and excess chemicals with a water taste standard (pH) that can be consumed is 6.5 to 9.2 and is included in the minimum limit of total dissolved solids (TDS). Therefore, in this study, a measuring instrument was designed consisting of criteria included in clean and healthy water standards that are easy to apply close to the industrial environment. This study aims to (1) find out the system of designing tools to measure water quality with IoT-based Arduino Uno technology, (2) knowing the telecommunications process that occurs in sensors integrated into the internet, and (3) knowing the analysis results of water quality measuring devices with IoT-based Arduino Uno technology. This study conducted testing of water samples in industrial areas. The test was carried out with 3 types of sensors, namely pH sensors, TDS sensors, and turbidity sensors controlled by microcontrollers. The results of this study show the level of pH, dissolved solids and the level of turbidity in water that can be monitored anytime and anywhere through an application while connected to the internet. With this tool, it greatly facilitates the stage of testing pollutants in rivers, it is proven that in one test, it can produce 3 data with different parameters.